Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea - Murao, Ryuki (Zootaxa, 2017)
The South Korean fauna of the Hemihalictus series belonging to the genus Lasioglossum Curtis are reviewed. Twenty-seven species are recognized for the country. Lasioglossum laevoides Ebmer is recorded from the Korean Peninsula for the first time. The following species are newly recorded from South Korea: L. albipes villosum Ebmer, L. calceatum (Scopoli), L. kiautschouense (Strand), L. sakagamii Ebmer, L. speculinum (Cockerell), L. subfulvicorne subfulvicorne (Blüthgen), L. villosulum (Kirby), and L. vulsum (Vachal). Illustrated keys to females and males of South Korean species are provided. Bionomical data such as flight and flower records in South Korea are given.